2022
DOI: 10.3389/frai.2022.835298
|View full text |Cite
|
Sign up to set email alerts
|

Backchannel Behavior Influences the Perceived Personality of Human and Artificial Communication Partners

Abstract: Different applications or contexts may require different settings for a conversational AI system, as it is clear that e.g., a child-oriented system would need a different interaction style than a warning system used in emergency situations. The current article focuses on the extent to which a system's usability may benefit from variation in the personality it displays. To this end, we investigate whether variation in personality is signaled by differences in specific audiovisual feedback behavior, with a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The results revealed a positive association between a higher number of identified BOPs and elevated levels of agreeableness, conscientiousness and openness. This is in line with the results of an earlier study that showed that different types of backchannel behavior correlate with various impressions of people's specific personalities (Blomsma et al, 2022).…”
Section: Current Worksupporting
confidence: 92%
See 1 more Smart Citation
“…The results revealed a positive association between a higher number of identified BOPs and elevated levels of agreeableness, conscientiousness and openness. This is in line with the results of an earlier study that showed that different types of backchannel behavior correlate with various impressions of people's specific personalities (Blomsma et al, 2022).…”
Section: Current Worksupporting
confidence: 92%
“…In a follow-up experiment, we showed that the type of backchannel behavior indeed influences the personality perception of the listener. Listeners who produced head nods with a bigger amplitude are, for example, perceived as being more extraverted, compared to listeners whose head nods are smaller (Blomsma et al, 2022).…”
Section: Variability Between Addresseesmentioning
confidence: 99%
“…Non-verbal cues also play a significant role in the perception of personality [6]. This has been shown in studies of gaze [7], back channels [8] and body language cues [9].…”
Section: Introductionmentioning
confidence: 85%
“…Different backchannel formulation methods have been implemented and tested in HRI, from copying the actual backchannels of a human listener in the same conversation ( Gratch et al., 2007 ; Poppe et al., 2011 ; Blomsma et al., 2022 ), over learning from observing human listeners and formulating rules ( Gratch et al., 2007 ; Al Moubayed et al., 2009 ) or from data using machine learning approaches ( Adiba et al., 2021 ), to hand-crafted backchannels deemed suitable for the robot at hand ( Park et al., 2017 ; Murray et al., 2022 ). Backchannels specifically created for robots include head nods ( Fujie et al., 2004 ; Al Moubayed et al., 2009 ; Park et al., 2017 ; Murray et al., 2022 ), gaze and eyebrow movement ( Park et al., 2017 ), smiling ( Al Moubayed et al., 2009 ; Park et al., 2017 ) and short utterances ( Fujie et al., 2004 ; Park et al., 2017 ; Sebo et al., 2020 ).…”
Section: Previous Workmentioning
confidence: 99%
“…Natural backchanneling is also challenging for conversational agents and robots and numerous studies ( Gratch et al., 2007 ; Al Moubayed et al., 2009 ; Poppe et al., 2011 ; Inden et al., 2013 ; Hussain et al., 2019 ; Sebo et al., 2020 ; Adiba et al., 2021 ; Blomsma et al., 2022 ; Murray et al., 2022 ) have been devoted to endowing social robots and agents with a human-like and/or adequate backchannel strategy. It has been shown that the robot’s backchanneling affects how human subjects perceive it ( Gratch et al., 2007 ; Blomsma et al., 2022 ) and it is thus a key factor for successful spoken human-robot interaction (HRI).…”
Section: Introductionmentioning
confidence: 99%